Grid Parameter estimation using Model Predictive Direct Power Control - Arif, Bilal; Tarisciotti, Luca; Zanchetta, Pericle; Clare, Jon C.; Degano, Marco (IEEE, 2015)
This paper presents a novel Finite Control Set Model Predictive Control (FS-MPC) approach for grid-connected converters. The control performance of such converters may get largely affected by variations in the supply impedance, especially for systems with low Short Circuit Ratio (SCR) values. A novel idea for estimating the supply impedance variation, and hence the grid voltage, using an algorithm embedded in the MPC is presented in this paper. The estimation approach is based on the difference in grid voltage magnitudes at two consecutive sampling instants, calculated on the basis of supply currents and converter voltages directly within the MPC algorithm, achieving a fast estimation and integration between the controller and the impedance estimator. The proposed method has been verified, using simulation and experiments, on a 3-phase 2-level converter.